Boundedness of Area Functions Related to Schrödinger Operators and Their Commutators in Weighted Hardy Spaces (Analysis in Theory and Applications, 2022)
In this paper, we consider the area function $S_Q$ related to the Schrödinger operator $\mathcal{L}$ and its commutator $S_{Q,b}$, establish the boundedness of $S_Q$ from $H^p_ρ(w)$ to $L^p(w)$ or $WL^p(w),$ as well as the boundedness of $S_{Q,b}$ from $H^1_ρ(w)$ to $WL^1(w).$